The chamomile aromatherapy reduce the scale of nausea - Ima Nurcahyanti Putri; Rizky Amelia; Sri Rahayu (International Journal of Public Health Science (IJPHS), 2019)
The incidence of cervical cancer in the world is 17 per 100,000 women, while the mortality rate ranges from 8.2 per 100,000 women. One therapy for cancer treatment is chemotherapy. The side effects caused by chemotherapy are nausea and vomiting. In addition to drugs, complementary therapy given to chemotherapy patients is chamomile aromatherapy. This study aims to determine the effect of chamomile aromatherapy on reducing the scale of nausea after chemotherapy of cervical cancer patients in Dr. Moewardi Hospital. The type of research used is quasy experiment, using a research design non equivalent with the control group pretest and posttest design. The sample used was 30 patients with the criteria of patients who experienced Acute & Delayed Nausea. Analyze data used Paired Samples Test and Independent T-Test. The results showed that the average scale of nausea before chamomile aromatherapy intervention was 15.40. And the average scale of nausea after intervention was 2.87 as evidenced by the value p=0.000 (p<0.05). The average value of the nausea after treatment scale in the control group was 7.33, and the nausea scale average value in the intervention group was 2.87. So that it can be concluded that there is an effect after being given chamomile aromatherapy to reduce the scale of nausea after chemotherapy with p=0.000.